Latin America and Beyond: The Case for Comparative Area Studies - Hoffmann, Bert (European Review of Latin American and Caribbean Studies, 2015)
Comparative Area Studies (CAS) emerges as a new approach in which scholars of Latin American Studies engage systematically with scholars working on other world regions. Adopting a focus on intra-, inter- and cross area comparisons, CAS builds on the traditional strengths of area studies. At the same time it enables scholars to have a stronger impact on overarching conceptual debates and it may provide new bridges between area studies scholars and the academic communities in the regions studied. However, a comparative area studies approach requires systematic cooperation among scholars of different world regions, and adequate organizational and institutional structures to support them. Resumen: Latinoamérica y más allá: El caso de los estudios regionales comparativos Los Estudios Regionales Comparativos (Comparative Area Studies – CAS) surgen como un enfoque nuevo dentro del cual académicos de Estudios Latinoamericanos colaboran sistemáticamente con académicos que investigan sobre otras regiones del mundo. Tomando como punto de partida comparaciones intrarregionales, interregionales y transregionales, los ERC se basan en los puntos fuertes tradicionales de los estudios regionales. Al mismo tiempo, este enfoque permite a los académicos tener un impacto mayor en los debates conceptuales más amplios y puede tender nuevos puentes entre los académicos de estudios regionales y las comunidades académicas de las regiones estudiadas. Sin embargo, un enfoque de estudios regionales comparativos exige una cooperación sistemática entre académicos de distintas regiones del mundo y unas estructuras organizativas e institucionales adecuadas para apoyarles.